Architectural Approach to the Upper Floor of a Multi-Storey Conventional Market - Artika Zahra Nabila Agustin; Kania Kinasih (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2026)
Multi-storey conventional markets are designed to maximize the use of available space, but because of low visitor traffic, the higher levels are frequently underutilized. This issue suggests a connection between the degree of spatial activity and architectural design. In order to activate the upper floors of Multi-storey conventional markets, this study will look at architectural design strategies. A descriptive, qualitative approach with an architectural focus is employed, which includes observations of the building's physical state, accessibility and circulation systems, and space user behavior. The findings show that the increase in activity on the higher floors can be attributed to a number of factors, including accessibility, circulation clarity, and spatial appeal. It is anticipated that this study will be used as a guide for creating multi-storey conventional marketplaces that are more user-responsive and functional.